China, India and the contest for the Indo-Pacific. Issue 2 (1st November 2019) - Robertson, Peter; Yuan, Jingdong; Mudiyanselage, Harsha Konara
Abstract : Purpose: The purpose of this paper is to describe how China's rapid growth and increasing resource dependence have changed its relationship with India and their respective defense strategies. In particular, we consider China's Belt and Road Initiative, India's "Act East" policy and the strategic and economic value of the Indian Ocean and South China Sea regions. Design/methodology/approach: The authors find no econometric evidence of interactions between China and India's military spending using a Richardson-Baumol arms race model. Likewise, in a cross-county panel data study of military spending, they find that China's military spending has no independent effect on military spending in other countries. The authors also show that once wage costs and other sources of military inflation are accounted for, the pattern of real defense spending growth is much less intense than is suggested by nominal data. Nevertheless, they show that China has been undertaking intense military modernization with rapidly rising capital-labor ratios in its defense spending. Findings: The authors find little evidence of a traditional arms race, but also show that China, and to a lesser extent India, have been realigning their military capabilities to these new security risks while maintaining overall military burden on the economy. Research limitations/implications: Econometric analysis is limited by data availability and is necessarily historical, whereas the security situation is very fluid and may change in the short term. Practical implications: The paper identifies factors that are likely to influence China and India's attitudes to defense spending in the coming years. Social implications: The paper finds that there is not an arms race in the traditional sense but may be an arms race in terms of new technologies and military modernization. Originality/value: This is a very much underexplored topic in economics. The authors take an interdisciplinary approach showing how economics tools can be used to help understand this important issue in international relations.